Student perceptions on the benefits and shortcomings of distributed pair programming assignments - Xinogalos, Stelios; Satratzemi, Maya; Chatzigeorgiou, Alexander; Tsompanoudi, Despina (IEEE Global Engineering Education Conference, 2017)
Pair Programming (PP) has been extensively used for enhancing the learning of programming. Specifically, PP is considered to: make the learning of programming more pleasant, promote collaboration and communication between the members of pairs, encourage the sharing of knowledge and skills, and even improve code quality. More recently, systems have appeared that support Distributed Pair programming (DPP). DPP is considered to maintain all the benefits of PP and in addition to allow for the distributed collaboration of pairs from anywhere and at any time. However, DPP might impose limitations as well, such as the requirement from students to configure their systems and ensure a good Internet connection. In order to draw safer conclusions on the benefits and shortcomings of DPP and maximize its effects on the learning of programming, it is necessary to investigate its impact under real world situations. This research is twofold: the effect of DPP on student performance has to be thoroughly studied; student perceptions on the benefits and shortcomings of DPP have to be investigated in order to apply it in the best possible way. The study presented in this paper focuses on the latter issue. Specifically, student perceptions on DPP assignments carried out in the context of an Object-Oriented Programming (OOP) course based on Java throughout a whole semester are quantitatively and qualitatively analyzed. Based on this analysis some guidelines are presented for carrying out DPP assignments more effectively in the context of an OOP, Java-based course.